Rumen fermentation pattern, enzyme profile and ciliate protozoal population in betel (Piper betle) leaves fed lactating crossbred cows - SANTRA, A; KONAR, S; MANDAL, A; DAS, S K (The Indian Journal of Animal Sciences, 2016)
The aim of this study was to evaluate the effect of supplementation of Piper betle (local name ‘Pan’) leaf (Bangla variety) on rumen ciliate protozoal population, enzyme profile and fermentation characteristics in lactating crossbred cows. Twelve lactating crossbred (Jersey × Tharparker) cows with an average milk yield of 5.4 ± 0.78 kg/d were divided into equal groups (G1 and G2) and fed individually under stall feeding for 70 days on a mixed ration containing green fodder (maize) and concentrate mixture. The G1 group was supplemented with 100 g Piper betle leaves powder/animal/day along with concentrate mixture. No significant differences were noticed between the 2 groups for daily dry matter intake and nutrient digestibility. However, rumen pH, ammonia nitrogen concentration and total rumen protozoal as well as holotrich and spirotrich protozoal population decreased while ruminal TVFA and propionic acid production increased due to supplementation of Piper betle leaves. Rumen enzyme activities were similar in both the experimental group. It is concluded that supplementation of Piper betle leaves have a potential for reducing ciliate protozoal population and rumen ammonia nitrogen concentration without affecting rumen polysaccharide degrading enzyme activities and nutrient digestibility in dairy cow.